(untitled) - Mays, Larry W. (New York, NY., 2004)
Since 9/11, water supply protection has become an urgent and timely issue. This is the first comprehensive reference devoted exclusively to water system safety and security. Aimed at engineers, managers, operators, and analysts involved with the design, operation, maintenance, and rehabilitation of large and small water systems, this resource thoroughly examines every major infrastructure aspect of security and water safety. * Physical threats, chemical and biological threats, cyber threats, and emergency response plans * Actual case studies from the field * Explains how to develop an effective emergency management and response plan
Keywords: Waterworks,Water-supply,Terrorism; Security measures,Prevention